Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/pathogens9020072
|View full text |Cite
|
Sign up to set email alerts
|

Hypermutation as an Evolutionary Mechanism for Achromobacter xylosoxidans in Cystic Fibrosis Lung Infection

Abstract: Achromobacter xylosoxidans can cause chronic infections in the lungs of patients with cystic fibrosis (CF) by adapting to the specific environment. The study of longitudinal isolates allows to investigate its within-host evolution to unravel the adaptive mechanisms contributing to successful colonization. In this study, four clinical isolates longitudinally collected from two chronically infected patients underwent whole genome sequencing, de novo assembly and sequence analysis. Phenotypic assays were also per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 36 publications
2
30
0
1
Order By: Relevance
“…The hypermutator phenotype was detected in 20% of the isolates ( n = 11). Hypermutators have been found previously in A. xylosoxidans and other species isolated from CF infection, and it is assumed that the higher mutation rate has a positive effect on faster selection of adaptive phenotypes in this environment ( 14 , 25 , 49 , 54 , 55 ). It is also likely that this phenotype is fixed in CF1 as a result of its longer colonization in the patient, since it has been suggested that longer evolution history is associated with the hypermutator phenotype ( 56 ).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The hypermutator phenotype was detected in 20% of the isolates ( n = 11). Hypermutators have been found previously in A. xylosoxidans and other species isolated from CF infection, and it is assumed that the higher mutation rate has a positive effect on faster selection of adaptive phenotypes in this environment ( 14 , 25 , 49 , 54 , 55 ). It is also likely that this phenotype is fixed in CF1 as a result of its longer colonization in the patient, since it has been suggested that longer evolution history is associated with the hypermutator phenotype ( 56 ).…”
Section: Discussionmentioning
confidence: 90%
“…Infections of A. xylosoxidans have recently become more prevalent in patients with CF ( 5 , 6 , 9 ), but there are few studies that characterize the genetic adaptation of Achromobacter spp. in CF infections ( 24 , 48 , 49 ). To complement these studies, we used a combination of functional and genomic approaches to reflect on the biology of A. xylosoxidans adaptation in the CF model.…”
Section: Discussionmentioning
confidence: 99%
“…Libraries were prepared using the KAPA PCR-free kit (Roche Sequencing Solutions, Pleasanton, CA, USA) and sequenced on a NextSeq500 Illumina platform (Illumina, Hayward, CA, USA) generating 150bp paired end reads with a mean read yield of 10978104 and a mean coverage of 190X. Read quality controls, de novo assembly, and genome annotation were performed similarly to our previous work [ 35 ]. Details on the sequencing and de novo assembly are available in Table S2 .…”
Section: Methodsmentioning
confidence: 99%
“…Four isolates were previously analysed by Veschetti et al . (2020) (12) where patients A and B correspond to patients P0802 and P8603, respectively, in this study. The use of clinical isolates was approved by the local ethics committee at the Capital Region of Denmark (Region Hovedstaden; approval registration number H-4-2015-FSP), and the use of clinical registry data was approved by the Danish Agency for Patient Safety (approval registration number 31-1521-428).…”
Section: Methodsmentioning
confidence: 99%